The History of Islamic Education in Minangkabau: The Impact of the Paderi Movement on the Shift in Scholarly Orientation of Minangkabau Ulama - Ilham, Mhd; Syauqi, Khilal (Tafkir: Interdisciplinary Journal of Islamic Education, 2025)
The Paderi Movement was an Islamic purification movement that emerged in 19th-century Minangkabau, influenced by Wahhabi teachings. This study aims to analyze the shift in the scientific orientation of the Paderi Movement regarding the development of Islam in Minangkabau, particularly in the context of social conflict, changes in religious structures, and contributions to the modernization of Islamic education. Data collection was conducted through a literature study using manuscripts and books written by Minangkabau scholars from the 19th to the 20th century, which serve as historical documents. The analysis employs historical methods, applying heuristic techniques, source criticism, interpretation, and writing, with a social science approach to examine historical understanding empathetically (verstehen). The findings indicate that the Paderi Movement had a significant impact on the development of Islam in Minangkabau. Despite its proselytization methods causing conflicts with traditionalist groups and Sufi orders, the movement successfully introduced a more Sharia-based interpretation of Islam and promoted the modernization of Islamic education. Thus, the Paderi Movement was not merely a socio-religious phenomenon but also played a crucial role in shaping the intellectual structure of Islam in Minangkabau.